The Gut Microbiota (Microbiome) in Cardiovascular Disease and Its Therapeutic Regulation - Rahman, Md. Mominur; Islam, Fahadul; -Or-Rashid, Md. Harun; Mamun, Abdullah Al; Rahaman, Md. Saidur; Islam, Md. Mohaimenul; Meem, Atkia Farzana Khan; Sutradhar, Popy Rani; Mitra, Saikat; Mimi, Anjuman Ara; Emran, Talha Bin; Fatimawali,; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
In the last two decades, considerable interest has been shown in understanding the development of the gut microbiota and its internal and external effects on the intestine, as well as the risk factors for cardiovascular diseases (CVDs) such as metabolic syndrome. The intestinal microbiota plays a pivotal role in human health and disease. Recent studies revealed that the gut microbiota can affect the host body. CVDs are a leading cause of morbidity and mortality, and patients favor death over chronic kidney disease. For the function of gut microbiota in the host, molecules have to penetrate the intestinal epithelium or the surface cells of the host. Gut microbiota can utilize trimethylamine, N-oxide, short-chain fatty acids, and primary and secondary bile acid pathways. By affecting these living cells, the gut microbiota can cause heart failure, atherosclerosis, hypertension, myocardial fibrosis, myocardial infarction, and coronary artery disease. Previous studies of the gut microbiota and its relation to stroke pathogenesis and its consequences can provide new therapeutic prospects. This review highlights the interplay between the microbiota and its metabolites and addresses related interventions for the treatment of CVDs.